Nonlinear continuum mechanics of solids fundamental mathematical and physical concepts - Başar, Yavuz 1935-2002; Weichert, Dieter (Springer, 2000)
The aim of the book is the presentation of the fundamental mathematical and physical concepts of continuum mechanics of solids in a unified description so as to bring the young researchers rapidly close to their research area. Accordingly, emphasis is given to concepts of permanent interest and details of minor importance are omitted. The formulation is achieved systematically in absolute tensor notation which is almost exclusively used in modern literature. This mathematical tool is presented such that the study of the book is possible without permanent reference to other works